Bi2MoO6/BiVO4 heterojunction electrode with enhanced photoelectrochemical properties. Issue 7 (27th January 2016) - Ma, Ying; Jia, Yulong; Wang, Lina; Yang, Min; Bi, Yingpu; Qi, Yanxing
Abstract : Herein, we demonstrate the synthesis of a Bi2 MoO6 nanorod array followed by the deposition of a BiVO4 absorber layer. Abstract : Herein, we demonstrate the synthesis of a Bi2 MoO6 nanorod array followed by the deposition of a BiVO4 absorber layer. This heterojunction yielded a photocurrent density of 250 μA cm −2 at 0.8 V SCE, which is 21 times that produced by a planar Bi2 MoO6 array under the same conditions. Moreover, in situ X-ray photoelectron spectroscopy clearly confirmed the improvement of the electron transport and charge separation afforded by the heterostructure, features that efficiently enhanced the photoelectrochemical properties of the array.